What constitutes a majority in Curaçao Government? An analysis of the results of Curaçao’s March 2021 elections - Goede, Miguel; Meent, Everardus van de (Archives of Business Research, 2021)
The objective of this case study is to examine the current electoral system of Curaçao to ascertain whether it provides adequate representation of its constituents. The current system is imbalanced because it favors the larger political parties disproportionally, which leads to a distortion of the will of the voter. The results from the most recent election held in March 2021 were compiled and examined. An alternative system was considered to gain insight into the detrimental effects of the current system. An evaluation of the current system employed to allocate seats after the election were found to be inequitable, suggesting that measures should be taken to enhance the legitimacy of the system by better reflecting the will of the voters. Given that it has been decades since the system was examined, this research provides an updated foundation for considering alternative allocation procedures that would be more consistent with a healthy representative democracy.